2016
DOI: 10.1007/s11842-016-9338-x
|View full text |Cite
|
Sign up to set email alerts
|

New Forest Owners: Change and Continuity in the Characteristics of Swedish Non-industrial Private Forest Owners (NIPF Owners) 1990–2010

Abstract: This paper presents a total survey of the characteristics and changes over time within the entire population of Swedish non-industrial private forest owners (NIPF owners). By charting the changed demographic, socio-economic and geographic profile of the NIPF owners, it also provides a baseline for a discussion and analysis of potential implications for forest management, policy and values. NIPF owners differ in important ways from the general population of Sweden. However, the gap has narrowed over time with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…The explanatory approach employed in this study adds to the descriptive statistical and qualitative approaches previously used to explore gender dimensions in forest management (e.g. Lidestav and Nordfjell 2005;Lidestav 2010;Andersson and Lidestav 2016;Haugen et al 2016) and may be used in other contexts to explore how gender matters for natural resource management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The explanatory approach employed in this study adds to the descriptive statistical and qualitative approaches previously used to explore gender dimensions in forest management (e.g. Lidestav and Nordfjell 2005;Lidestav 2010;Andersson and Lidestav 2016;Haugen et al 2016) and may be used in other contexts to explore how gender matters for natural resource management.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, compared to their male counterparts, a larger proportion of female owners in, for example, Sweden, Norway, Finland, and France have university degrees and are non-resident owners (Follo et al 2016;Haugen et al 2016). Even though structural differences could potentially explain lower levels of management among female owners, results by Coté et al (2016) indicated that gender differences persist even after controlling for size of forest, distance to forest, having a management plan, length of ownership, and education.…”
Section: Introductionmentioning
confidence: 99%
“…A high proportion of today's forest owners do not live on their properties, but reside in more urban environments (Haugen et al 2016). Previous research shows that forest owners who live on or adjacent to their forest estates view their holdings differently, and set different priorities to those who live in towns (Holmgren et al 2005;Nordlund and Westin 2011).…”
Section: Concluding Discussionmentioning
confidence: 99%
“…This correlates with the fact that female FFOs in this study have a higher level of education than male FFOs, and thus are potentially less economically dependent on their forest holdings (cf. Haugen et al 2016). However, it is obvious that none of the FFOs who participated in this study are driven exclusively by profit.…”
Section: The Views Of Ffos On Forest Social Valuesmentioning
confidence: 93%
“…In the context of rural change, urbanization and globalization, there is an ongoing transformation of the private forest owner corps in European countries and the US towards increased heterogeneity in terms of their socio-economic characteristics, objectives, and values (e.g., Kvarda 2004;Hogl, Pregernig, and Weiss 2005;Kendra and Hull 2005;Rickenbach, Zeuli, and Sturgess-Cleek 2005;Wiersum, Elands, and Hoogstra 2005;Fischer et al 2010;Urquhart and Courtney 2011;Haugen, Karlsson, and Westin 2016). Growing numbers of private forest owners 1 are no longer directly dependent on their forestland for their livelihood and their relationships to their forests go beyond financial considerations to a wide range of values and meanings, such as nature conservation, recreation, and personal enjoyment (Kvarda 2004;Kendra and Hull 2005;Wiersum, Elands, and Hoogstra 2005;Ingemarson, Lindhagen, and Eriksson 2006;Nordlund and Westin 2011;Urquhart and Courtney 2011).…”
Section: Introductionmentioning
confidence: 99%